Riau Malay Language Reduplication in Medan City Village, Kelayang District, Indragiri Hulu Regency - Nurbaina; Ermawati Sulaiman; Alber (UIR Press, 2022)
Each word will not occur reduplication without a morphological process. The morphological process includes giving affixes, reduplication or repetition of words, and combining words. So, reduplication or repetition of words is part of the morphological process. This research method is descriptive method. Data collection techniques in this study used recording techniques, fishing techniques and note-taking techniques. The data analysis technique used descriptive data with procedures for classifying data, describing data reduplication, analyzing language reduplication, interpreting data and concluding. The results of this study are the reduplication of Riau Malay Language in Medan City Village, Kelayang District, Indragiri Hulu Regency, consisting of pure reduplications found as many as 62 Pure reduplication data, for example: [dapuɣ-dapuɣ] 'dapur-dapur', while 5 sound-changing reduplications, for example: [bola-baliɁ] 'back and forth', while 5 Partial reduplications for example: [trees]'trees', while 10 Affixed reduplications for example: [luŋguɁ-luŋguɁkan] 'collect-collect